Generative Design: an overview and its relationship to Artificial Intelligence - Borsodi, Eszter; Takács, Ágnes (Design of Machines and Structures, 2022)
The paper deals with generative design. It presents the definition and the pro-cess of generative design and mentions the differences from traditional design method. The application areas are also discussed with real life examples and collection of possible application cases. Furthermore, the article analyses the connection between Artificial In-telligence and generative design and gives a suggestion for adapting Deep Learning in the evaluation and selection phase.